The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/joc.6920
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the March Arctic Oscillation on the South China Sea summer monsoon onset

Abstract: This study reveals that the South China Sea summer monsoon (SCSSM) onset is closely linked to the preceding March Arctic oscillation (AO), the dominant mode of atmospheric circulation over extratropical Northern Hemisphere. The physical processes for the impact of the March AO on the SCSSM onset are further examined. March AO leads to an anomalous low-level cyclone over subtropical western North Pacific (WNP) via eddy-mean flow interaction. The southwesterly wind anomalies to the southeastern side of the anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…2a,b,3c,d). These findings correspond with those from Hu et al (2021), and they demonstrated that the equatorward displacement of the WNP cyclone induced by the positive March AO favors the early onset of the South China Sea summer monsoon. Previous studies have indicated the role of the WNP atmospheric circulation anomalies on the development of IOD (Kajikawa et al 2003;Huang and Shukla 2007).…”
Section: Atmospheric Circulation Associated With March Nao From Sprin...supporting
confidence: 87%
See 1 more Smart Citation
“…2a,b,3c,d). These findings correspond with those from Hu et al (2021), and they demonstrated that the equatorward displacement of the WNP cyclone induced by the positive March AO favors the early onset of the South China Sea summer monsoon. Previous studies have indicated the role of the WNP atmospheric circulation anomalies on the development of IOD (Kajikawa et al 2003;Huang and Shukla 2007).…”
Section: Atmospheric Circulation Associated With March Nao From Sprin...supporting
confidence: 87%
“…2a-c, 3c-d, 4a-c; Gong et al 2011). Moreover, Rossby wave response associated with positive diabatic heating has the strongest westerly wind to the south of the heating center (Gill 1980;Hu et al 2021); accordingly, warm SSTAs and cyclonic circulations develop equatorward (Fig. 2a-c, 3c-d, 4a-c).…”
Section: Atmospheric Circulation Associated With March Nao From Sprin...mentioning
confidence: 95%
“…One reason is that springtime AO has a direct impact on the East Asian Summer Monsoon precipitation over East Asia (Gong et al ., 2011; Chen et al ., 2015a). And, by modulating the tropical Pacific SST and ENSO, AO could also impact the monsoon activity over East Asia (Chen et al ., 2014; 2015b; Hu et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The onset of the SCSSM, which has been studied and debated for decades, is not a novel topic (Xie et al, 1998;Lu and Chan, 1999;Ding and Chan, 2005;Mao and Chan, 2005;Ronghui et al, 2006;Wen et al, 2006;Ding et al, 2008;Wang et al, 2009;Wu, 2010;Hu et al, 2020Hu et al, , 2021. However, studying the roles of SSWs in the SCSSM onset may provide additional insights.…”
Section: Roles Of Ssws and Both Isos In The Maintenance Stage Of The ...mentioning
confidence: 99%